TRANSFORMASI PEMBELAJARAN AGAMA ISLAM MELALUI E-BOOK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - nur habibah, eka putri; Atika Agustina Tarik; Ah. Zakki Fuad (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
The development of information and communication technology provides great opportunities for transforming learning, especially Islamic Religious Education (PAI) at SMP Panglima Sudirman Surabaya. This study aims to examine the utilization of e-books as a learning medium for PAI and its effect on students’ learning motivation. The research method used is descriptive qualitative with subjects including teachers, students, and the principal. Data were collected through observation, interviews, questionnaires, documentation, and focus group discussions. The results show that the use of e-books significantly increases students’ learning motivation, with 56% of students demonstrating high motivation. E-books provide a more interactive, engaging, and flexible learning experience while enhancing students’ digital literacy. The main challenges are limited devices and infrastructure, but with proper support, e-books have the potential to be an effective solution for innovative and contextual PAI learning. This study is expected to serve as a reference for the development of digital learning in other schools.